Association between dyslipidaemia and the risk of hyperuricaemia: a six-year longitudinal cohort study of elderly individuals in China - Xu, Ying; Dong, Haoyu; Zhang, Boya; Zhang, Jiayu; Ma, Qinghua; Sun, Hongpeng (Annals of medicine (Helsinki), 2022)
Despite abundant evidence linking dyslipidaemia to an increased risk of hyperuricaemia, the exact association between each component of dyslipidaemia and hyperuricaemia remains controversial. Thus, the objective of this research was to examine the correlation between dyslipidaemia and its components, as well as hyperuricaemia in Chinese people over the age of 60. In this study, 4018 participants over 60 years without hyperuricaemia were investigated from 2014 to 2020. The association between each dyslipidaemia component and hyperuricaemia was evaluated employing Cox proportional hazards models. This research conducted further stratified and sensitivity analyses to assess the potential relationship. A total of 1155 participants suffered from hyperuricaemia (28.75%) at the time of the 6-year follow-up survey. In multivariable-adjusted analyses, compared to participants with normal lipid levels, those with dyslipidaemia had 1.28 times the risk (95% confidence interval 1.12 to 1.47) of experiencing hyperuricaemia. The hazard ratios (HR) (95% CI) comparing high TC, high TG, high LDL-C, and low HDL-C of dyslipidaemia with the regular group were 0.99 (0.72 to 1.37), 1.30 (1.07 to 1.57), 1.02 (0.70 to 1.50), and 1.20 (1.00 to 1.44), respectively. There was a nonlinear dose-response between TG, HDL-C, and serum uric acid (SUA). Dyslipidaemia and its two distinct types, high TG and low HDL-C, increased hyperuricaemia incidence in this prospective cohort. Further research should be undertaken to investigate the possible reverse causality between different components of dyslipidaemia and hyperuricaemia.